Penegakan Hukum Pernikahan Perceraian di Era Digital Apa Tantangan dan Solusinya - Andy Satria; Grace Aprillia P Manullang; Mesy Nadya Sidabutar; C.Septia Dinda Sinaga (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
In the current global era, easy access to the Internet is very important. Why not, everyone has a device that makes it easier to navigate cyberspace. This comfort certainly affects expressions that were previously expressed through the real world, but the virtual world is absorbing more and more of it. There are many situations in the household where husbands and wives communicate more via devices, there by neglecting their responsibilities. The adverse effects brought about by social media result in conflict either due to indifference or jealousy on the part of the spouse becomes excessively acquainted with social media. One of the reasons an intriguing factor in divorce cases involves the utilization of social media.